Trajectories of parental and peer supply of alcohol in adolescence and associations with later alcohol consumption and harms: A prospective cohort study. (1st August 2022) - Aiken, Alexandra; Chan, Gary; Yuen, Wing See; Clare, Philip J.; Hutchinson, Delyse; McBride, Nyanda; Najman, Jackob M.; McCambridge, Jim; Upton, Emily; Slade, Tim; Boland, Veronica C.; De Torres, Clara; et al.
Abstract: Background: Supply of alcohol to adolescents is associated with increased alcohol consumption and harms including alcohol use disorder (AUD). We aimed to identify: (1) trajectories of alcohol supply to adolescents; (2) sociodemographic characteristics associated with supply trajectory; (3) patterns of alcohol consumption by supply trajectory; and (4) supply trajectory associations with adverse alcohol outcomes. Methods: We used Australian longitudinal survey data (N = 1813) to model latent trajectories of parent and peer alcohol supply over five annual follow-ups (Waves 2–6; Mage 13.9–17.8 years). Regression models assessed associations between supply trajectories and Wave 1 (Mage =12.9 years) sociodemographic factors and associations between supply trajectories and Wave 7 (Mage =18.8 years) alcohol outcomes. Results: We identified five alcohol supply classes: (1) minimal supply (n = 739, 40.8%); (2) early parent sips, late peer/parent whole drinks (n = 254, 14.0%); (3) late peer/parent whole drinks (n = 419, 23.1%); (4) early parent sips, mid peer/parent whole drinks (n = 293, 16.2%); (5) early peer/parent whole drinks (n = 108, 6.0%). Compared to minimal supply, the other classes were 2.7–12.9 times as likely to binge drink, 1.6–3.0 times as likely to experience alcohol-related harms, and 2.1–8.6 times as likely to report AUD symptoms at age 19. Conclusion: Earlier supply of whole drinks, particularly from peers, was associated with increased risk of early adulthood adverse alcohol outcomes. While minimal supply represented the lowest risk, supplying sips only in early-mid adolescence and delaying supply of whole drinks until late adolescence is likely to be less risky than earlier supply of whole drinks. Highlights: There is wide variation in the quantity and timing of parent and peer supply of alcohol in adolescence. No supply of alcohol during adolescence had the lowest risk of alcohol use problems at age 19. Sips in early-mid adolescence and delaying whole drinks was associated with less risk than early whole drinks. Earlier supply of whole drinks, particularly more peer than parent supply, was associated with the greatest risk.